Levels of F2-isoprostanes, F4-neuroprostanes, and total nitrate/nitrite in plasma and cerebrospinal fluid of patients with traumatic brain injury. (2nd December 2015) - Yen, H.-C.; Chen, T.-W.; Yang, T.-C.; Wei, H.-J.; Hsu, J.-C.; Lin, C.-L.
Abstract : Several events occurring during the secondary damage of traumatic brain injury (TBI) can cause oxidative stress. F2 -isoprostanes (F2 -IsoPs) and F4 -neuroprostanes (F4 -NPs) are specific lipid peroxidation markers generated from arachidonic acid and docosahexaenoic acid, respectively. In this study, we evaluated oxidative stress in patients with moderate and severe TBI. Since sedatives are routinely used to treat TBI patients and propofol has been considered an antioxidant, TBI patients were randomly treated with propofol or midazolam for 72 h postoperation. We postoperatively collected cerebrospinal fluid (CSF) and plasma from 15 TBI patients for 6–10 d and a single specimen of CSF or plasma from 11 controls. Compared with the controls, the TBI patients exhibited elevated levels of F2 -IsoPs and F4 -NPs in CSF throughout the postsurgery period regardless of the sedative used. Compared with the group of patients who received midazolam, those who received propofol exhibited markedly augmented levels of plasma F2 -IsoPs, which were associated with higher F4 -NPs levels and lower total nitrate/nitrite levels in CSF early in the postsurgery period. Furthermore, the higher CSF F2 -IsoPs levels correlated with 6-month and 12-month worse outcomes, which were graded according to the Glasgow Outcome Scale. The results demonstrate enhanced oxidative damage in the brain of TBI patients and the association of higher CSF levels of F2 -IsoPs with a poor outcome. Moreover, propofol treatment might promote lipid peroxidation in the circulation, despite possibly suppressing nitric oxide or peroxynitrite levels in CSF, because of the increased loading of the lipid components from the propofol infusion.